Interaction of the effects associated with auditory-motor integration and attention-engaging listening tasks - Wikman Patrik; Rinne Teemu (Elsevier Ltd, 2022)
A number of previous studies have implicated regions in posterior auditory cortex (AC) in auditory-motor integration during speech production. Other studies, in turn, have shown that activation in AC and adjacent regions in the inferior parietal lobule (IPL) is strongly modulated during active listening and depends on task requirements. The present fMRI study investigated whether auditory-motor effects interact with those related to active listening tasks in AC and IPL. In separate task blocks, our subjects performed either auditory discrimination or 2-back memory tasks on phonemic or nonphonemic vowels. They responded to targets by either overtly repeating the last vowel of a target pair, overtly producing a given response vowel, or by pressing a response button. We hypothesized that the requirements for auditory-motor integration, and the associated activation, would be stronger during repetition than production responses and during repetition of nonphonemic than phonemic vowels. We also hypothesized that if auditory-motor effects are independent of task-dependent modulations, then the auditory-motor effects should not differ during discrimination and 2-back tasks. We found that activation in AC and IPL was significantly modulated by task (discrimination vs. 2-back), vocal-response type (repetition vs. production), and motor-response type (vocal vs. button). Motor-response and task effects interacted in IPL but not in AC. Overall, the results support the view that regions in posterior AC are important in auditory-motor integration. However, the present study shows that activation in wide AC and IPL regions is modulated by the motor requirements of active listening tasks in a more general manner. Further, the results suggest that activation modulations in AC associated with attention-engaging listening tasks and those associated with auditory-motor performance are mediated by independent mechanisms.